Prediction model for the selection of patients with glioma to proton therapy - Jesper Folsted Kallehauge; Siri Grondahl; Camilla Skinnerup Byskov; Morten Høyer; Slavka Lukacova (Acta Oncologica, 2025)
Background and purpose: The selection of patients with low-grade gliomas for proton therapy (PT) is often based on the comparison of photon and PT plans and demonstrating meaningful dose reduction to the healthy brain or critical structures. The aim of this retrospective study was to identify clinical parameters associated with referral to PT and build a prediction model.